The American journey - Appleby, Joyce (Glencoe/McGraw-Hill, 2002)
The American Journey is a superb, readable presentation of American history, from pre-exploration to the present. Its unparalleled author team, including the National Geographic Society, ensures accuracy in every detail of the narrative, maps, and charts.